(3QhVI GdYbdGAs - (3eMeO Hf MHGf Hf CMeO Hf MHGf Hf eYGP Hf eYHO GdJejej, CHh MGJe GdHSJj, hjbGd dg GHf MHGf,J (B354 (3g` s ((3jhSa s)
(3ChdgG (B:s
(3HMLI MJi jSQi bGVjkG , hdGjTch GdhLY EdG YfO ef jQLh YfOg GdHQA , hdG jeOM CMOkG ZdG HeG ajg s
(3BNQgG (B:s
(3bO PcQfG GdjSjQ ef GdcKjQ ef GdGKGQ , hGdbdjd ef GdLSje ef GdCNHGQ ai cJGHfG gPG LYdfG Gddg eef OYJg JHGTjQ GdJhajb Edi GdbjGe HMbGFb GdJMbjb hUdi Gddg Ydi eMeO NGJe GdfHjjf s
(3HgG fXGe GdJYbjHIs
(3Ydi ghGeTgG ebGHdI Ydi fSN CNQi hJUMjMGJs
(3HChdgG JedcGJ eMOKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs